2018
DOI: 10.1007/s00705-018-3968-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of an attenuated porcine epidemic diarrhea virus strain by serial passaging

Abstract: Porcine epidemic diarrhea virus (PEDV) is prevalent in most parts of the world. Owing to its antigenic variation, prevention of the diseases caused by this virus is difficult. In this study, two PEDV isolates with similar growth kinetics were successfully propagated in Vero cells. Complete genome sequence analysis showed that they have a 49nt deletion in the ORF3 gene and were classified into Group 1, the same group that includes the classical CV777 strain. Recombination analysis revealed that the event had oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…PEDV LAVs based on classical (G1) strains have been applied in Asian countries ( 11 ), but their efficacies against the emerging highly virulent (G2) strains were minimal, probably due to the antigenic difference between the S proteins of G1 and G2 strains ( 12 ). To develop G2 PEDV LAVs, we and other research groups have previously applied the traditional method of attenuation via serially passaging virulent G2 isolates in Vero cells ( 13 20 ). Although these LAV candidates were attenuated sufficiently in pigs, they usually failed to consistently induce adequate protective immunity against challenge with the virulent G2 strains ( 16 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…PEDV LAVs based on classical (G1) strains have been applied in Asian countries ( 11 ), but their efficacies against the emerging highly virulent (G2) strains were minimal, probably due to the antigenic difference between the S proteins of G1 and G2 strains ( 12 ). To develop G2 PEDV LAVs, we and other research groups have previously applied the traditional method of attenuation via serially passaging virulent G2 isolates in Vero cells ( 13 20 ). Although these LAV candidates were attenuated sufficiently in pigs, they usually failed to consistently induce adequate protective immunity against challenge with the virulent G2 strains ( 16 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Porcine epidemic diarrhea virus (PEDV), transmissible gastroenteritis virus (TGEV), and rotavirus (PoRV) are the main causes of porcine viral diarrheal disease through individual or mixed infections [ 1 ]. PEDV is a single-stranded positive-strand alpha coronavirus with a length of approximately 28 kb.…”
Section: Introductionmentioning
confidence: 99%
“…Recombination in PEDV is also a widespread phenomenon. Several reports have identified recombinant sequences (Supplementary Table S3) in the PEDV S gene ( Qin et al, 2019 ), ORF1a ( Jie et al, 2018 ), and ORF1b ( Chen et al, 2017 ); recombination across multiple genes has also been shown ( Jarvis et al, 2016 ). Among CoVs, homologous RNA recombination is a major factor underlying genetic evolution and diversity ( Ntafis et al, 2011 ; Woo et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%